Enhancing The Quality and Cost Control Team's Role in Improving Primary Care Referrals in Bantaeng. - Wahidah, Muhayyina; Yuliana Sari, Andi Rifika; Prasetiya, Ihwan; Firdaus, Firdaus; Ahmad, St. Musdalifah (Jurnal Jaminan Kesehatan Nasional, 2025)
This study evaluates how well the Quality and Cost Control Team (TKMKB) can improve referral quality by reviewing and medically auditing Non-Specialist Referral Rasio (RRNS) indicators with the First Level Health Facility (FKTP). The quantitative descriptive approach compares RRNS data with Time, Age, Complication, and Comorbidity (TACC). It evaluates the appropriateness of TACC criterion selections before and after implementing the medical audit and RRNS indicator review with TACC at FKTP in Bantaeng Regency. The FKTPs that were sampled were those that met RRNS indicators at Ulugalung Health Center, Kota Health Center, and Pabentengang Health Center in Bantaeng Regency, had KBK compensation, and achieved 100% KBK for six consecutive months. The study results show that non-specialist referrals (RNS) with TACC were lower than those with RRNS TACC before the review and medical audit intervention. In Bantaeng District, 92.05% of referrals were Specialist Referrals, while 7.95% were Non-Specialist Referrals (0.92% RNS without TACC and 7.03% RNS with TACC). Additionally, following the TKMKB intervention, TACC criteria for Time were also reduced, suggesting an increase in the quality of referrals, particularly in selecting TACC criteria at FKTP in compliance with current norms and guidelines. Thus, the Branch Quality and Cost Control Team's contribution to enhancing referral quality via the medical audit and assessment of RRNS indicators with TACC at FKTP is deemed successful.